Sunday

April 20, 2014

April 20, 2014

Posted by **Zoey** on Saturday, March 6, 2010 at 4:37pm.

y= 3-secx/tanx

- calculus -
**bun**, Saturday, March 6, 2010 at 7:32pmy' = (3-secx)'tanx -(3-secx)(tanx)'/(tanx)^2

= -secx(tanx)^2 - (3-secx)secx/(tanx)^2

= -secx[(tanx)^2 + (3-secx)]/tan^2x

=-[(tan)^2 +3 -secx]/sinx

- calculus -
**joans**, Thursday, August 30, 2012 at 10:29amY=-cosxln(secx+tanx)

**Related Questions**

Calculus - find the derivative of f(x)=tanx-4/secx I used the quotient rule and ...

Math - I can't find the integral for (tanx)^(6)*(secx)^(2) I tried splitting up ...

precal- PLEASE HELP! - secx/secx-tanx=sec^2x+ secx+tanx

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Calculus - find the derivative y= csc^-1 (secx) 0 less than or equal to x less ...

Trig - Verify the identity. (secx + tanx)/(secx - tanx) = (1 + 2sinx + sin(^2)x...

Trig - Verify the identity. 1/(tanx-secx) + 1/(tanx+secx) = -2tanx

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Precalculus - (cosxcotx/secx+tanx)+(sinx/secx-tanx)

Trig - Verify the identity: tanx/secx-1=secx+1/tanx